Macroeconomics : understanding the global economy - Miles, David (David D.); Scott, Andrew, 1965-; Breedon, F. J. (Francis J.) (Chicester, West Sussex : John Wiley and Sons, Inc., 2012)
"A revised and updated edition of a very successful macroeconomics t extbook. The authors deal with sophisticated issues using advanced econ omic theory, but in a manner that is accessible to anyone taking a sing le course in macroeconomics. They begin with real-world economic issues , and describe why these matter, before embarking on economic theory, e nsuring that readers emerge with a good practical understanding of the global economy and how economists think about it"--
Machine generated contents note: Introduction -- 1. What is Macroeco nomics? 2. The Language of Macroeconomics: The National Income Accounts -- Economic Growth and the Supply side. 3. The Wealth of Nations - the Supply Side. 4. Capital Accumulation and Economic Growth. 5. Total Fac tor Productivity, Human Capital, and Technology. 6. Endogenous Growth a nd Convergence. 7. Unemployment and the Labor Market. 8. International Trade. 9. Globalization. -- Business Cycles and Economic Policy -- 10. Consumption and Investment 11. Business Cycles 12. Money and Prices 13. Monetary Policy 14. Fiscal policy and the Role of the Government 15. S tabilization Policy 16. Financial Markets: Equities and Bonds 17. The B anking Sector 18. Sovereign Debt and Default -- Exchange Rates and Glob al Capital Markets 19. Exchange rate determination: the real exchange r eate 20. Exchange rate determination: nominal exchange rates and asset markets 21. Currency Crises and Exchange Rate Systems.
Revised edition of: Macroeconomics and the global business environme nt / David Miles, Andrew Scott. 2nd ed.
Includes bibliographical references and index.
Keywords: Macroeconomics; BUSINESS & ECONOMICS / Economics / Macroeconomics